The Impact Of Arabic-Translated Books On Arabic Language Learning In Sri Lanka - Mohideen, HLM. (Bumi Lingua Edu Center, 2024)
Translation is a critical conduit for cross-cultural communication, facilitating the exchange of ideas and knowledge across linguistic boundaries. By overcoming language barriers, translation grants individuals access to global scientific and literary resources, promoting international cooperation, mutual understanding, and sustainable development. In Sri Lanka, Muslim scholars have shown a marked interest in translating Arabic texts into local languages, driven by a desire to tap into the rich Arab cultural and scientific heritage and to extract this knowledge accessible to speakers of the island's native languages. The translation of these texts seeks to enrich the local culture and enhance education within Sri Lankan communities and aims to convey a correct understanding of Islam and its teachings, thereby promoting cooperation and coexistence in a society characterized by ethnic and religious diversity. Moreover, these translations play a significant role in teaching Arabic to non-native speakers. This study investigates the role of translated Arabic texts in enhancing the language skills of Arabic learners in Sri Lanka, evaluates the impact of these translations on students' understanding of Arabic culture, and explores the challenges students face when learning Arabic through translated materials. The research employs descriptive and analytical methodologies, with data collected through a questionnaire administered via Google Forms to students studying Arabic at government universities in Sri Lanka. The findings indicate that students in Sri Lanka heavily depend on translated Arabic texts to learn the language, as these resources assist them in comprehending complex vocabulary and are regarded as reliable, with an accuracy rate of up to 97%. Translators employ various strategies to address translation challenges, interpreting these texts as valuable and appropriate for the student's needs. The study underscores the essential role of these translations in improving language proficiency among Arabic learners in Sri Lanka.